ANTECEDENTS OF PURCHASE BEHAVIOR IN LOCAL SKINCARE USERS - Maretta, Widy Ariesty; Pratomo, Luki Adiati (Tekmapro, 2025)
This study was conducted to examine the influence of a celebrity influencer's credibility, celebrity influencer attractiveness, online customer review, and perceived expertise on attitude, examining the impact of attitude on purchase intention and the influence of purchase intention on purchase behavior on local skincare products. The type of research used is causality research, which aims to test the influence of one variable on other variables. The variables used consisted of 4 independent variables (celebrity influencer's credibility, celebrity influencer attractiveness, online customer review, and perceived expertise), two mediation variables (attitude and purchase intention), and 1 dependent variable (purchase behavior). The sampling technique uses purposive sampling with a number determination technique using Hair et al., 2019; the number of samples is 5 times the number of indicators, 30. The data collection results showed that the number of samples was 205 (minimum sample 150). The analysis technique used is the Structural Equation Model (SEM) using AMOS 23 software. The findings showed that a celebrity influencer's credibility was not proven to have a positive effect on attitude, a celebrity influencer's attractiveness was proven to have a positive effect on attitude, online customer reviews were not proven to have a positive effect on attitude, perceived expertise was proven to have a positive effect, the attitude was proven to have a positive effect on purchase intention, and purchase intention had a significant positive impact on purchase behavior.